Female entrepreneurship and religious tourism in Ecuador [Emprendimiento femenino y turismo religioso en Ecuador] - Armas Herrera, R. (2016)
The general object of this research, exploratory in nature, to analyze the main factors influencing female entrepreneurship, through religious tourism in Ecuador. The empirical research used logistic regression models (Logit), information obtained through surveys of a sample of women entrepreneurs in business lines related to: relics, handicrafts, textiles, candles, hotels, gastronomy, tour operators, tourist attractions and religious. The main results emphasize that age; motivation; education; religious tourism; access to financial credit and financial amounts are the most significant keys to promoting female entrepreneurship. The research is located at the theoretical level, with preliminary approach type, so that the results can be the basis for a subsequent applied research, slitting structured and stratified for whose development qualitative and quantitative methodologies will be employed.